Animals — Non-Animals, Humans — Non-Humans. Comic Heroes in Spitamegeranomachia by Jan Achacy Kmita - Goszczyńska, Aleksandra (The Motifs of Fauna and Flora in Literature and Culture, 2018)
The first Polish mock-heroic poem, the 16th century Spitamegeranomachia by Jan Achacy Kmita, is a playful and ingenious way of blurring the boundary between the human and animal worlds. This literary adaptation of the ancient Greek myth of the annual crusade attacks on small Pygmies (geranomachia) is a description of regular war in which birds were greatly humanized while at the same time the prestige of their human antagonist was lowered. Another origin of Kmita’s comic heroes was a paradoxography of the Historia naturalis by Pliny the Elder. It embraced images of semi-human, semi-animal creatures (hybrids) and human monsters, which enriched the image of the collective hero of the Spitamegeranomachia with another animal-non-animal and human-inhuman exempla.